Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd000215.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintics for people with neurocysticercosis

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 43 publications
0
30
0
1
Order By: Relevance
“…For viable parenchymal disease, antiparasitic medications increase the speed of radiographic resolution22 and decrease seizure recurrence 23. Albendazole (at 15 mg/kg/day by mouth for 8–15 days) is slightly more efficacious than praziquantel (at 50–75 mg/kg/day by mouth for 15 days) 24.…”
Section: Discussionmentioning
confidence: 99%
“…For viable parenchymal disease, antiparasitic medications increase the speed of radiographic resolution22 and decrease seizure recurrence 23. Albendazole (at 15 mg/kg/day by mouth for 8–15 days) is slightly more efficacious than praziquantel (at 50–75 mg/kg/day by mouth for 15 days) 24.…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary diagnostic criteria for neurocysticercosis have been established [10], and the medical treatment of neurocysticercosis, including considerations relating to the use of antihelminthic [1] and cysticidal agents, steroids, and antiepileptic drugs, have been reviewed by a number of groups [12,13,28,21]. Neurosurgical indications and approaches have also been studied [20,7,24,30,15] and reviewed by several authors [25,29].…”
Section: Discussionmentioning
confidence: 99%
“…In general, eradication therapy with cysticidal agents benefit symptomatic patients with multiple, live (non-calcified) cysticerci. A meta-analysis by Abba et al 25 found that administration of cysticidal therapy in patients with viable lesions reduced the number of lesions. Another study by Kalra et al 26 concluded that the combination of albendazole and dexamethasone increases resolution of NCC lesions and reduces the risk of recurrence of seizure among children presenting one or two ring-enhancing lesion on CT.…”
Section: Discussionmentioning
confidence: 99%